Visualizing antithrombin-binding 3-O-sulfated heparan sulfate motifs on cell surfaces. Issue 92 (4th November 2020) - Kalita, Mausam; Chua, Jie Shi; Boothello, Rio S.; Joice, April; Antelope, Orlando; Roy, Anindita; Anandh Babu, Pon Velayutham; Saijoh, Yukio; Desai, Umesh R.; Kuberan, Balagurunathan
Abstract : To map the cellular topography of the rare 3- O -sulfated structural motif of heparan sulfate (HS), we constructed quantum dot-based probes for antithrombin and FGF2, which reveal widely different distribution of the targeted HS motifs. Abstract : To map the cellular topography of the rare 3- O -sulfated structural motif of heparan sulfate (HS), we constructed quantum dot-based probes for antithrombin and FGF2, which reveal widely different distribution of the targeted HS motifs. The technology helps show that old and young aortic endothelia display widely different levels of the antithrombin-binding 3- O -sulfated HS motif.